(untitled) (Global Journal of Medical Research, 2016)
Diabetes Mellitus (DM) has type-1 & type 2. So in diabeties type-2 is very severe disease which creates complications and effect on various part of body. Most sensitive part of body is Eye which is affected by DM responsible in progression of Diabetic Retinopathy (DR). DR is a slowly effects on eye & come to focus when the changes on the retina have progressed to a level at which treatment turns complicate, so an early diagnosis and referral to an ophthalmologist or optometrist for the management of this disease can prevent 98% of severe visual loss. The aim of this work is to automatically identify Diabetic Retinopathy (DR), and Background Retinopathy using fundus images. Our results show a classification accuracy of 92%, with sensitivity and specifity of 95%.